Numerical Wave Tank Analysis for Energy Harvesting with Oscillating Water Column - Yamac, Halil Ibrahim; Koca, Ahmet (Springer International Publishing Ag, 2018)
In this study, analysis of Oscillating Water Column which is one of the Wave Energy Converters is made in Numerical Wave Tank base on Fluent consist of Finite volume Method. NWT is simulated based on Reynolds-averaged Navier-Stokes equations. Volume of Fluid method, k-epsilon turbulence model, Pressure Implicit with Splitting of Operator algorithm Dynamic Mesh Technique are employed in transient numerical analysis. User Defined Function is introduced for movement of Piston Type wave maker. The hydrodynamic energy absorbed from the waves by the OWC device during a wave period is calculated for two cases have different shore slopes at the same volume of water in tank. The comparison of two cases shows that the increase in the shore slope angle means decrease in the output power in air chamber of OWC device at the same volume of water.
12th International Conference on Mechatronics -- SEP 06-08, 2017 -- Brno, CZECH REPUBLIC
Keywords: Wave energy harvesting; Oscillating Water Column; Numerical; Wave Tank; Volume of Fluid; Shore slope effects